Pengaruh Afirmasi Diri terhadap Tingkat Kecemasan pada Pasien Pre Operasi - Sri Saptiningsih; Endang Supriyanti (Journal of Medical Practice and Research, 2026)
Anxiety is a common psychological response experienced by preoperative patients, arising from concerns about surgical outcomes, pain, potential complications, and fear of death. This condition can affect both physiological and psychological stability and may hinder the recovery process. One simple intervention to reduce anxiety is self-affirmation, a cognitive-behavioral approach that utilizes positive statements. This study aims to analyze the effect of self-affirmation on anxiety levels among preoperative patients in the Mawar ward of RSUD Kajen. The study employed a pre-experimental method with a pretest-posttest design. A total of 60 respondents were selected using purposive sampling. The instruments used included a standard operating procedure (SOP) for self-affirmation and the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data were analyzed using the Wilcoxon test. The results showed that all respondents experienced moderate anxiety before the intervention, which decreased after self-affirmation to mild anxiety (16.7%) and moderate anxiety (83.3%). Statistical analysis indicated that all respondents experienced a reduction in anxiety (negative rank = 60) with a p-value of 0.000 (p < 0.05). It is concluded that self-affirmation is effective in reducing anxiety among preoperative patients.